Kochland eaudiobook The secret history of koch industries and corporate power in america. - Leonard, Christopher (Simon & Schuster Audio, 2019)
NEW YORK TIMES BESTSELLER * NEW YORK TIMES NOTABLE BOOK OF 2019 * WINNER OF THE J ANTHONY LUKAS WORK-IN-PROGRESS AWARD * FINANCIAL TIMES' BEST BOOKS OF 2019 * NPR FAVORITE BOOKS OF 2019 * FINALIST FOR THE FINACIAL TIMES/MCKINSEY BUSINESS BOOK OF 2019 * KIRKUS REVIEWS BEST BOOKS OF 2019 * SCHOOL LIBRARY JOURNAL BEST BOOKS OF 2019 "Superb...Among the best books ever written about an American corporation." — Bryan Burrough, The New York Times Book Review Just as Steve Coll told the story of globalization through ExxonMobil and Andrew Ross Sorkin told the story of Wall Street excess through Too Big to Fail , Christopher Leonard's Kochland uses the extraordinary account of how one of the biggest private companies in the world grew to be that big to tell the story of modern corporate America. The annual revenue of Koch Industries is bigger than that of Goldman Sachs, Facebook, and US Steel combined. Koch is everywhere: from the fertilizers that make our food to the chemicals that make our pipes to the synthetics that make our carpets and diapers to the Wall Street trading in all these commodities. But few people know much about Koch Industries and that's because the billionaire Koch brothers have wanted it that way. For five decades, CEO Charles Koch has kept Koch Industries quietly operating in deepest secrecy, with a view toward very, very long-term profits. He's a genius businessman: patient with earnings, able to learn from his mistakes, determined that his employees develop a reverence for free-market ruthlessness, and a master disrupter. These strategies made him and his brother David together richer than Bill Gates. But there's another side to this story. If you want to understand how we killed the unions in this country, how we widened the income divide, stalled progress on climate change, and how our corporations bought the influence industry, all you have to do is read this book. Seven years in the making, Kochland "is a dazzling feat of investigative reporting and epic narrative writing, a tour de force that takes the reader deep inside the rise of a vastly powerful family corporation that has come to influence American workers, markets, elections, and the very ideas debated in our public square. Leonard's work is fair and meticulous, even as it reveals the Kochs as industrial Citizens Kane of our time" (Steve Coll, Pulitzer Prize–winning author of Private Empire ).